SINERGI KECERDASAN EMOSIONAL DAN GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA AUDITOR - Siti Nurlatifah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to analyze the influence of the synergy between emotional intelligence and leadership style in improving auditor performance at Public Accounting Firms (KAP) in the South Jakarta area. The research employs a quantitative approach using a survey method, with nonprobability sampling techniques and saturated sampling for data collection. Data were gathered through questionnaires that had been tested for validity and reliability. A total of 65 questionnaires were returned and processed. Data analysis was conducted using multiple linear regression and hypothesis testing. The results show that emotional intelligence and leadership style have a positive and significant impact on auditor performance. Additionally, there is a significant interaction between emotional intelligence and leadership style in influencing auditor performance. This study provides new insights by examining the interaction of these two variables in the context of auditor performance at KAP in South Jakarta. The practical implications of this study include recommendations for developing emotional intelligence and implementing effective leadership styles to enhance auditor performance.